2020
DOI: 10.1158/0008-5472.can-19-2883
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Involved in Tumorigenesis Are Over-Represented in Mutated Active DNA-Binding Sites in Neuroblastoma

Abstract: The contribution of coding mutations to oncogenesis has been largely clarified, whereas little is known about somatic mutations in noncoding DNA and their role in driving tumors remains controversial. Here, we used an alternative approach to interpret the functional significance of noncoding somatic mutations in promoting tumorigenesis. Noncoding somatic mutations of 151 neuroblastomas were integrated with ENCODE data to locate somatic mutations in regulatory elements specifically active in neuroblastoma cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…invasion by affecting the proper expression of downstream signaling molecules. [3][4][5] Therefore, the expression levels of TFs and their regulatory products (e.g., mRNAs, proteins, miRNAs, and lncRNAs) have been investigated to establish strategies for cancer diagnosis, prognosis, and evaluation of therapeutic responses. [6][7][8] As a result, several candidate TFs associated with tumor progression were identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…invasion by affecting the proper expression of downstream signaling molecules. [3][4][5] Therefore, the expression levels of TFs and their regulatory products (e.g., mRNAs, proteins, miRNAs, and lncRNAs) have been investigated to establish strategies for cancer diagnosis, prognosis, and evaluation of therapeutic responses. [6][7][8] As a result, several candidate TFs associated with tumor progression were identified.…”
mentioning
confidence: 99%
“…30 When deregulated, this transcriptional regulatory pattern plays a crucial role in the occurrence and progression of multiple cancers by mediating intracellular or intercellular signal transduction and regulating tumorassociated downstream signaling pathways. 3,4,13,31 It was speculated that the above-mentioned regulatory relationship between TFs and membrane proteins exists between MACC1 and SPINT1 because of their molecular characteristics. Even though both MACC1 and SPINT1 were validated to be associated with the HGF/c-Met signaling pathway in multiple cancer types, synergistic regulations of MACC1 and SPINT1 in the context of the HGF/c-Met signaling axis and the potential pan-cancer prognostic value of these two gene combinations remain to be investigated.…”
mentioning
confidence: 99%
“…The first variant (rs6239) was found to alter the motifs of the CCNT2 gene, located on chromosome 2, which plays a role in mitosis [26] and in regulating p53 activity, which is critically impaired in different cancers [29]. The second variant, rs16885980, has been found to disrupt the activity of different transcription factors (TF) in the PRL gene -Foxc1_2, Foxd1_, Maf_disc2, YY1_disc1, and YY1_known5 -which further regulates the expression many driver genes of cancers [45][46][47]. The third variant, rs1205955, is in strong linkage with variant rs1205960 (r 2 ≥ 0.8) and has the ability to potentially alter the PRL gene transcription motifs such as AFP1, Mef2_known1, Mef2_known6, Ncx_2, Pax-4_2, Pou2f2_known8 and TATA_known.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies, high-throughput sequencing and microarray gene expression-based studies have identified multiple genetic changes that characterize NB -both hereditable and somatically acquired [6][7][8][9][10][11] . Genetic alterations occurring in noncoding DNA such as TERT rearrangements 12 and point mutations in regulatory elements of transcription factor binding sites 13 also contribute to NB development. However, several recurrent segmental chromosomal alterations (SCA) have been demonstrated to better discriminate between low-risk and high-risk patients with fatal outcomes 10,11 .…”
Section: Introductionmentioning
confidence: 99%